Is it in a neonate's best interest to enter a randomised controlled trial?. Issue 2 (1st April 2001) - Allmark, Peter; Mason, Su; Gill, A Bryan; Megone, Christopher
Abstract : Clinicians are required to act in the best interest of neonates. However, it is not obvious that entry into a randomised controlled trial (RCT) is in a neonate's best interest because such trials often involve additional onerous procedures (such as intramuscular injections) in return for which the neonate receives unproven treatment or a placebo. On the other hand, neonatology needs to develop its evidence base, and RCTs are central to this task. The solution posited here is based on two points. First, "best interest" is not equivalent to "the best possible interest" only to "best interest within a certain realm". The realm of deliberation when asking the title question is the neonate's health. Deliberating in this realm may involve the exclusion from consideration of some factors that might be thought relevant (such as parental wealth). Furthermore, circumstances may dictate the need to deliberate on other factors that might be thought irrelevant (such as health care resources). Second, deciding on a neonate's best interest does not involve "putting oneself in its shoes". Rather, it involves asking in what it has an interest, or stake. These will include some things in which we all, as human beings, have a stake, such as medical progress. Putting these two points together, in the realm of health the answer to whether RCT entry is in a neonate's best interest is usually very finely balanced. Where this is the case, it is reasonable to invoke a broader notion of best interest and include a broader range of elements in which the neonate has a stake, including medical progress. In this way RCT entry can, usually, be said to be in a neonate's best interest.